Effect of La2O3 addition on microstructure, morphology and pressure sensing behaviour of PZT based ceramics sintered in Al2O3 environment - Mohammad Hafizuddin, Hj. Jumali; Tio, Ying Ying; Norhashimah, Ramli; Muhammad, Mat Salleh; Muhammad, Yahaya (Universiti Malaysia Perlis, 2010)
International Conference on X-Rays and Related Techniques in Research and Industry (ICXRI 2010) jointly organized by Universiti Malaysia Perlis (UniMAP) and X-Ray Application Malaysia Society (XAPP), 9th - 10th June 2010 at Aseania Resort Langkawi, Malaysia